Finite Element Analysis of Violin Bridge - Abu Bakar, Khairunnisa (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Violin is a string instrument, usually with four strings tuned in perfect fifths. Violin is the smallest, meanwhile, the highest pitched including viola, cello and double bass which comes from violin family. Since the engineering technology development nowadays, an improvement is successfully created which needed to cope with musician problem faced. Currently technology, pickup application was used as a transducer to amplify the sound of music. However, based on this project, determine the mounting position of sound transducer at the violin bridge is one of the possible alternatives. In order to analyze the bridge whereby can install the sensor at the optimum position, finite element analysis is the solution. Before start the FEA, the study of string tension which is the force applied into the bridge. Force analysis is divided into two which is force in static condition and after pickering. Generally, there are two bow movements which is move to the right and to the left. Actually, CATIA software has the application of finite element analysis besides able to do the modeling. Therefore, by using CATIA, it can analyze the bridge that is stressed and analyzed for specific results. In addition, by using CATIA software, it also can trace the complex shape of the bridge